2015
DOI: 10.1155/2015/283036
|View full text |Cite
|
Sign up to set email alerts
|

HPV Testing from Dried Urine Spots as a Tool for Cervical Cancer Screening in Low-Income Countries

Abstract: Nowadays, several screening strategies are available to prevent cervical cancer, but inadequate resources, sociocultural barriers, and sampling issues impede their success in low-income countries. To overcome these issues, this study aimed to evaluate the performance of human papillomavirus (HPV) testing from dried urine spots (DUS). Eighty-eight urine samples (including 56 HPV DNA positive specimens) were spotted on filter paper, dried, and stored in paper-bags. HPV DNA was detected from the DUS after 1 week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Previously published studies have in fact reported a high prevalence of the HPV 51 genotype in Italian women [15,18,19]. The high prevalence of HPV 16 is in keeping with the worldwide spread of this genotype, not only among women but also in the male population [6,9,14,20,21].…”
Section: Discussionmentioning
confidence: 75%
“…Previously published studies have in fact reported a high prevalence of the HPV 51 genotype in Italian women [15,18,19]. The high prevalence of HPV 16 is in keeping with the worldwide spread of this genotype, not only among women but also in the male population [6,9,14,20,21].…”
Section: Discussionmentioning
confidence: 75%
“…Epidemiological and biological studies found that HPV16 is the most frequently detected HPV genotype in patients with cervical cancer worldwide [6]. Moreover, it is also the predominant infection identified among subjects with or without genital lesions in different groups of the population [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Another much less utilized, but very similar sampling approach is the analysis of dried urine on filter paper, called dried urine strips (DUS). This approach has previously been used in other applications such as creatinine testing [ 25 , 26 ], HPV (human papillomavirus) testing [ 27 ], and metabolomics analysis [ 28 , 29 ]. Herein, we report on a DBS/DUS-HILIC-LC-MS/MS protocol development for analysis of the human blood and urine metabolome ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%